2017
DOI: 10.1111/cen.13301
|View full text |Cite
|
Sign up to set email alerts
|

First trimester isolated maternal hypothyroxinaemia: adverse maternal metabolic profile and impact on the obstetrical outcome

Abstract: The prevalence of hypothyroxinaemia in early pregnancy was of 8·7%. IH is associated with an increased maternal BMI and is related with a risk of breech presentation, a significant increase in macrosomia and caesarean sections. Screening should consider overweight as risk factor for hypothyroxinaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…Thyroid dysfunction during pregnancy is a matter of concern today, due to its widespread presence in pregnant women and the potential risk to children’s neurodevelopment. However, its relationship with clinical obstetric trimester variation is still controversial (17, 18, 19). The aetiology of IMH is still not well known, but iodine deficiency is proposed as a main one (20).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid dysfunction during pregnancy is a matter of concern today, due to its widespread presence in pregnant women and the potential risk to children’s neurodevelopment. However, its relationship with clinical obstetric trimester variation is still controversial (17, 18, 19). The aetiology of IMH is still not well known, but iodine deficiency is proposed as a main one (20).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this negative result, which may have been due to differences in women’s average age and ethnicity, most studies have clearly indicated adverse pregnancy outcomes for IMH. European research that included 879 pregnant women found that IMH during the early pregnancy was associated with an increased risk of macrosomia compared with a control group [ 17 ]. Women with hypothyroxinemia had significantly increased BMI from preconception to the time of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies are thus vulnerable to a high risk of false positive findings; therefore, further studies are needed. Other studies showed association between maternal isolated hypothyroxinemia with breech presentation or Cesarean section (28), preeclampsia (29) and macrosomia (11,28), the results from these isolated observational studies require additional confirmation. Thus, current evidence continues to support the statements made in the 2017 ATA Guidelines regarding isolated hypothyroxinemia in pregnancy.…”
Section: C) Treatment Of Subclinical Hypothyroidism (Question 37)mentioning
confidence: 85%